Measurement of the CKM angle γ in B± → DK± and B± → Dπ± decays with D → K0Sh+h- - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2021)
A measurement of CP-violating observables is performed using the decays B± → DK± and B± → Dπ±, where the D meson is reconstructed in one of the self-conjugate three-body final states K0Sπ+π− and K0SK+K− (commonly denoted K0Sh+h−). The decays are analysed in bins of the D-decay phase space, leading to a measurement that is independent of the modelling of the D-decay amplitude. The observables are inter- preted in terms of the CKM angle γ. Using a data sample corresponding to an integrated luminosity of 9 fb−1 collected in proton-proton collisions at centre-of mass energies of 7, 8, and 13 TeV with the LHCb experiment, γ is measured to be (68.7+5.2−5.1)∘. The hadronic parameters rDKB, rDπB ,δDKB, and δDπB, which are the ratios and strong-phase differences of the suppressed and favoured B± decays, are also reported.
Im Titel sind jeweils "±", "+", "-" und "0" hochgestellt, "S" ist tiefgestellt, dabei steht "0" über "S"
Gesehen am 15.03.2021